Enhancement of Solubility of Lamotrigine by Solid Dispersion and Development of Orally Disintegrating Tablets Using 32 Full Factorial Design. (27th October 2015) - Singh, Jatinderpal; Garg, Rajeev; Gupta, Ghanshyam Das
Abstract : Present investigation deals with the preparation and evaluation of orally disintegrating tablets (ODTs) of lamotrigine using β -cyclodextrin and PVP-K30 as polymers for the preparation of solid dispersion which help in enhancement of aqueous solubility of this BCS CLASS-II drug and sodium starch glycolate (SSG) and crospovidone as a superdisintegrating agent, to reduce disintegration time. The ODTs were prepared by direct compression method. Nine formulations were developed with different ratios of superdisintegrating agents. All the formulations were evaluated for disintegration time, weight variation, hardness, friability, drug content uniformity, wetting time, and in vitro drug release study. In vitro drug release study was performed using United States Pharmacopoeia (USP) type 2 dissolution test apparatus employing paddle stirrer at 50 rpm using 900 mL of 0.1 N HCl maintained at 37°C ± 0.5°C as the dissolution medium. On the basis of evaluation parameters formulations were prepared using β -CD 1 : 1 solid dispersion. Then 3 2 full factorial design was applied using SSG and crospovidone in different ratios suggested by using design expert 8.0.7.1 and optimized formulation was prepared using amount of SSG and crospovidone as suggested by the software. The optimized formulation prepared had disintegrating time of 15 s, wetting time of 24 s, and % friability of 0.55.